Transient receptor potential canonical 3 (TRPC3) channels are required for hypothalamic glucose detection and energy homeostasis - Chrétien, Chloé (2017)
Fil: Chrétien, Chloé. University of Bourgogne Franche-Comté. Institut National de la Recherche Agronomique. Centre des Sciences du Goût et de l’Alimentation; France